2005
DOI: 10.1161/circulationaha.104.491530
|View full text |Cite
|
Sign up to set email alerts
|

Freedom From Atrial Tachyarrhythmias After Catheter Ablation of Atrial Fibrillation

Abstract: Background-Data on the comparative value of the circumferential pulmonary vein and the segmental pulmonary vein ablation for interventional treatment of atrial fibrillation are limited. We hypothesized that the circumferential pulmonary vein ablation approach was superior to the segmental pulmonary vein ablation approach. Methods and Results-One hundred patients with highly symptomatic atrial fibrillation were randomly assigned to undergo either circumferential (nϭ50) or segmental pulmonary vein ablation (nϭ50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
184
0
8

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(201 citation statements)
references
References 33 publications
9
184
0
8
Order By: Relevance
“…The technique of performing wider linear ablations in the LA may aid in targeting different substrates that help to maintain or perpetuate AF. However, these techniques can be associated with challenges such as incidence of LA flutter (8) and complications such as atrioesophageal fistula. Furthermore, achieving complete linear block in certain anatomical regions (particularly the mitral isthmus) can be difficult (7).…”
Section: Discussionmentioning
confidence: 99%
“…The technique of performing wider linear ablations in the LA may aid in targeting different substrates that help to maintain or perpetuate AF. However, these techniques can be associated with challenges such as incidence of LA flutter (8) and complications such as atrioesophageal fistula. Furthermore, achieving complete linear block in certain anatomical regions (particularly the mitral isthmus) can be difficult (7).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] The mechanism(s) underlying development of organized atrial tachyarrhythmias in these patients as reported by various investigators remains inconsistent. One reason for this inconsistency is the use of terms atrial tachycardia (AT) and flutter interchangeably to describe these arrhythmias.…”
Section: Incidence and Mechanismsmentioning
confidence: 97%
“…An interesting observation in this context is that centers utilizing wide area circumferential PV ablation without necessarily confirming isolation report a higher prevalence (10-24%) of macro-reentrant atypical LA flutters. 2,5,9 In contrast centers that utilize PV isolation alone have observed a low overall incidence of organized atrial tachycarrhythmias and these have predominantly been focal, originating from in and around the reconnected PV segments. 1,7,8,11 In a prospective randomized comparison of segmental PV isolation versus wide area circumferential anatomical PV ablation, Karch et al reported a significantly higher occurrence of organized atrial tacycardias in the latter group (18% versus 2%).…”
Section: Incidence and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature shows varying result [7][8][9][10] , both because of differences in patient selection and because of the efficacy of these techniques 9,11,12 ; thus, there is no consensus as to which is the best therapeutic option for the control of AF patients. Also, most of these studies show results after more than one intervention and with usually short follow-up periods, thus possibly overestimating the procedural success.…”
Section: Introductionmentioning
confidence: 99%